2008
DOI: 10.1371/journal.pone.0002360
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Analysis of Erythrocyte microRNA Expression in Sickle Cell Diseases

Abstract: BackgroundSince mature erythrocytes are terminally differentiated cells without nuclei and organelles, it is commonly thought that they do not contain nucleic acids. In this study, we have re-examined this issue by analyzing the transcriptome of a purified population of human mature erythrocytes from individuals with normal hemoglobin (HbAA) and homozygous sickle cell disease (HbSS).Methods and FindingsUsing a combination of microarray analysis, real-time RT-PCR and Northern blots, we found that mature erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
199
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(211 citation statements)
references
References 43 publications
10
199
0
2
Order By: Relevance
“…The cycle threshold (2 Ϫ⌬⌬Ct ) method was utilized to calculate the fold change. As normalization of the miRNA data is critical in elimination of the bulk of false positives, the most stably expressed genes across the arrays, including three of the manufacturer-provided housekeeping genes (U6, 4.5S, and Y1) and miR152, were used to normalize the expression data; expression of these genes was unchanged across the arrays and time points as determined by NormFinder (8).…”
Section: Methodsmentioning
confidence: 99%
“…The cycle threshold (2 Ϫ⌬⌬Ct ) method was utilized to calculate the fold change. As normalization of the miRNA data is critical in elimination of the bulk of false positives, the most stably expressed genes across the arrays, including three of the manufacturer-provided housekeeping genes (U6, 4.5S, and Y1) and miR152, were used to normalize the expression data; expression of these genes was unchanged across the arrays and time points as determined by NormFinder (8).…”
Section: Methodsmentioning
confidence: 99%
“…Several miRNAs participate in the regulation of erythropoiesis: miR-221/222 inhibit normal erythropoiesis and erythroleukemic cell growth down-regulating kit receptor expression, 28 miR-24 hampers erythropoiesis by targeting ALK4 and perturbing activin signaling, 39 miR-320 finely tunes the translational activities of CD71 in reticulocytes, 20 c-Myb and miR-15a form an autoregulatory feedback loop which govern the transition from BFU-E to CFU-E stage. 40 Our results suggest that also miR-223 belongs to a functional set of miRNAs implicated in fine-tuning the expression of key genes to a physiologically relevant level during erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The commitment of pluripotent precursors to the erythroid lineage and the differentiation of committed erythroid progenitors into erythrocytes are associated with the induction or repression of several miRNAs. [16][17][18][19][20] However, the majority of their target genes are predicted computationally and only a few targets have been validated so far, preventing delineation of miRNAbased control circuitries.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique miRNA expression pattern in each cell-type the relative proportions of cells in blood may have an effect on the overall miRNA expression profile and the expression of their protein targets ( Min et al , 2010). Some studies have shown that mature miRNA expression signature in erythrocytes is similar to that in whole blood while different when compared to PBMCs ( Chen et al , 2008). MiR-451-5p is a marker of erythrocytes ( Rasmussen et al , 2010) and miR-23a-3p is unaffected by haemolysis ( Blondal et al , 2013).…”
Section: Discussionmentioning
confidence: 99%